Laparoscopically assisted colonoscopic polypectomy – viable option for curative surgery in elderly patients - Rokas Račkauskas; Saulius Mikalauskas; Marius Petrulionis; Tomas Poškus; Valdemaras Jotautas; Juozas Stanaitis; Eligijus Poškus; Kęstutis Strupas (Videosurgery and Other Miniinvasive Techniques)
Introduction : Colorectal cancer (CRC) is the third most common cancer worldwide and the fourth most frequent cause of cancer-related death in the world. CRC screening programs have been widely introduced worldwide, allowing for early detection and removal of precancerous lesions and avoiding major surgical intervention. However, not all polyps are suitable for conventional and advanced colonoscopic polypectomy. Thus, laparoscopically assisted colonoscopic polypectomy (LACP) was introduced to clinical practice as a method of choice for these polyps and adenomas. Aim: To overlook our experience in laparoscopically assisted colonoscopic polypectomies and evaluate effectiveness and quality of the procedure. Material and methods : A retrospective analysis of a prospectively maintained database was performed. using the Vilnius University Hospital Santariskiu Klinikos patient database for the period from 2010 to 2016, resulting in 21 cases in which LACP was performed. All procedures were performed using combined laparoscopy and videocolonoscopy techniques. Morphology of adenomas was classified according to the Paris classification during the procedure. Creation of the database was approved by the Lithuanian Bioethics committee. Results: Twenty-two adenomas were removed from 21 patients, aged 65.33 ±8.9. There was no difference between male and female age, but occurrence of adenomas in females was 2-fold higher. The majority of removed lesions were localized in the cecum and mean size was 27.2 ±11.1 mm. The morphology of adenomas was distributed equally between 0–Is, 0–Ip, and 0–IIa, except one, which belonged to 0–III. Histological analysis revealed that tubulovillous adenoma occurrence was 1.4 times higher than tubulous adenoma. There was only one postoperative complication – bleeding from the adenoma resection site, which was managed by conservative means. One patient developed G2 adenocarcinoma at the polyp resection site and was referred for radical surgery. Conclusions : The LACP is a safe procedure with minimal risk to the elderly patient. Patient follow-up is essential for detection of recurrence.